Facilitating E-learning through National Knowledge Network - P., Geetha; Cherukulath, Wilson K.; Sivakumar, R. (DESIDOC Journal of Library & Information Technology, 2017)
Learning is very important in the current knowledge based society. The economy of a country depends on the education level attained by the population of that country. Traditional learning cannot satisfy the various demands of the people. Due to the rapid growth in Information and Communication Technology (ICT) more and more innovative methods for accessing and sharing knowledge develop as the days pass. Government is keen on the integration of technology in educational programmes which are cost effective as well as time saving. E-learning or electronic learning is one such idea which is gaining momentum at a very fast pace. The new digital technologies used in e-learning are capable of meeting the user requirements at a high level. For all these a high bandwidth Internet connection is required. The National Knowledge Network (NKN) established by the government of India is mainly for sharing knowledge between research institutions. The e-learning facility has been started in Technical Information Resource centre (TIRC) of Naval Physical and Oceanographic Laboratory (NPOL) in 2014. This paper presents the different e-learning platforms which have been used through National Knowledge Network (NKN) to access e-learning programmes in NPOL. It also points out the increasing user demands for e-learning facility and the importance of librarians in the e-learning environment.